Project-Based Learning as a Method to Strengthen Communication: Students' Insights in Business English Education - Erna Dwinata; Rosanita Tritias Utami (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study examines students' perceptions of Project-Based Learning (PBL) in the